RESEÑA de: Ogando, Iolanda; Tato, Laura (ed.). Textos recuperados de Galo Salinas a Castelao. A Coruña : Universidade da Coruña, 2012 - Castro Otero, Salvador (Revista de lenguas y literaturas catalana, gallega y vasca, 2013)
-